The Small Prose of Oshakan: Panorama of Manners and Customs - GHAZARIAN, MARINE (Bulletin of Yerevan University B: Philology, 2021)
Hakob Oshakan with his stories, "tales" and "serious novels" primarily saved from forgetting his place of birth - Armenian village. Armenian village with its live, behavior and manners, psychological and moral world has become the axis of Oshakan’s literature. The purpose of Oshakan is the description of the rural world and its people, revealing the manners of this world. This was one of the important tasks in the system of his aesthetic views. Each story of Oshakan with its unique and colorful accent became a unified vivid picture of the Armenian rural nature, customs and manners, and their combination – a panorama of the village.The prose of Oshakan is a panorama of the life, festivals and rituals, manners and customs of a patriarchal Armenian village. Oshakan shows all this not only by descriptions but also with the promptness of mental discovery of heroes. Otherwise, hewould be considered as an eco-collector and ethnographer. Oshakan’s works, which describe the village, become a special triumph not only for people but also for exploring the national forgotten, even celebrated, or typical of some areas holidays. In these works, it can be seen also Oshakan’s great desire of salvation of the spiritual culture of his native village. Even in the description of the  beauty of nature Oshakan fills the rural pictures with the description of manners and life of people. Oshakan uses a conversational style, folk proverbs, and sayings to preserve the color in the descriptions of rural life.
Keywords: small prose, the world of the village, holidays, customs, lifestyle, mode of life